DISPUTE OF CUSTOMARY LAND TENURE AND DOMINATION AND THE RESOLUTION IN BULELENG REGENCY - I Nyoman Sardana (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2018)
ABSTRACT Customary Land Tenure and Domination not infrequently can lead to disputes, such as custom land disputes that occurred in the customary village of Rules, Buleleng District. Therefore, efforts to resolve the dispute need to be known. How is the Implementation of Customary Land Tenure and Domination in Buleleng Regency as well as the Settlement? Furthermore, the type of research used in this study is empirical legal research. The results of this study indicated that (1) the implementation of Customary Land Tenure and Domination in Buleleng Regency is said to have legitimization due to the control and ownership of customary land especially in the village of Anturan, Buleleng Subdistrict, Buleleng Regency has been based on land tenure system according to customary law (2) The settlement of customary land dispute cases that occurred in Anturan Village and Buleleng District was preceded by mediation dispute settlement efforts, but because it could not be resolved through mediation so that the case of this customary land dispute was filed suit to the Singaraja District Court by examining the evidence and witnesses presented by both parties to the dispute. Keywords: Dispute, Customary Land, Land Tenure